(untitled) (Research, Society and Development, 2023)
Introduction: During the pandemic, occurrences of thromboembolic complications and endothelial dysfunctions associated with COVID-19 were observed. Thus, the pathophysiology of the mechanisms of action are not fully elucidated. Methods: Aiming at a better understanding of the associated mechanisms of endothelial function due to COVID-19, a systematic review was developeded out using index databases and a selection process in which the inclusion criteria were articles that addressed the mechanism of thrombotic events by endothelium dysfunction and publications that associate COVID-19 with thrombotic complications in adults up to 59 years of age. Conclusion: SARS-CoV-2 is associated with altered endothelial function by endothelial mechanisms induced by direct viral infection and injury, leading to changes in the angiotensin II/AT1 axis and inflammatory response.